Computational Insights in Identification of Proficient Transient Receptor Potential Vanilloid 1 Inhibitors: A Pathway for Extenuating Chemotherapy-Induced Peripheral Neuropathy - Dinesh Kumar Chandanapalli; Shristi Arya; Shailesh Mani Tripathi; Ashish Kumar; Arbaz Sujat Shaikh; Venkata Rao Kaki; Sandeep Sundriyal; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

“Optic nerve sheath diameter measurement in severe traumatic brain injury: a prospective study of its utility in clinical decision-making” - Jitender Chaturvedi; Ajay Kumar; Divakar Goyal; Sanjeev Kumar; Madhur Uniyal; Quamar Azam (Next Research, 2026)

Sustainable Soil Microbial Dynamics and Macronutrient Uptake in Strawberry (Fragaria × ananassa) Using Integrated Bioorganic Formulations - Praveen Verma; Suman Bodh; Jitender Kumar Chauhan (Applied Fruit Science, 2026)

Unveiling the subsurface fault complexities using a convolutional network: a study from the Upper Assam foreland basin, NE India - Jitender Kumar; Kalachand Sain (Computational Geosciences, 2026)

Curcuma longa Mitigates Monocrotophos-Induced Oxidative Stress and Apoptosis in Testicular Germ Cells: Insights into Its Cytoprotective Potential - Vishavjeet Rathee; Prerna Bikal; Anshu Siwach; Shalu Sharma; Jitender Kumar Bhardwaj (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Retraction Note: Molecular Approaches for Authentication and Identification of Medicinal Plants - Jitender Kumar; Kajal Choudhary; Shelja; Anukriti; Harsharan Singh; Ashwani Kumar; Pankaj Bagga (Plant Molecular Biology Reporter, 2026)

Crossroad Between Gut Microbiome and Ischemic Stroke: Underlying Pathways and Therapeutic Possibilities - Shivashish Dobhal; Meenakshi Kaushik; Prem Lata Manhas; Ankur Kumar; Priyanka Naithani; Prakamya Gupta; Hitaishi Kaushik; Manisha Naithani; Balram Ji Omar; Ashish Kothari; Akshat Uniyal; Yogendra Pratap Mathuria; et al. (Indian Journal of Microbiology, 2026)

Random forest assisted machine learning approach for delimiting fluid saturation: a study from sandstone reservoir, North Assam shelf - Jitender Kumar; Priyadarshi Chinmoy Kumar; Kalachand Sain (Carbonates and Evaporites, 2026)

Smart farming approaches in medicinal plant cultivation: a review of techniques, benefits, and sustainability - Sanjeev Khan; Nutan Pathania; Pawan Kumar; Rahul Kumar; Jitender Kumar; Nitesh Kumar; Arti Sharma (Planta, 2026)

Macrophage-targeted Hyaluronic-acid Coated Liposomes Bearing Ursolic Acid for Visceral Leishmaniasis: In Vitro Characterisation and Pharmacokinetic Analysis - Spandana Gollapalli; Soyal Sayyed; Pawan Devangan; Dinesh Kumar Chandanpalli; Nandkumar Doijad; Rahul Kumar; Jitender Madan (Current Microbiology, 2026)

Influence of Plant Growth Regulators on Growth, Yield and Fruit Quality of Strawberry Cv. ‘Camarosa’ Under Protected Conditions - Suman Bodh; Jitender Kumar Chauhan; Gopal Singh; Meera Devi; Divya Pandey (Applied Fruit Science, 2026)

A comprehensive review on recent advances in nanomaterial facilitated phytoremediation - Nitesh Kumar; Ruchika Devi; Sushila Devi; Somvir Singh; Anand Singh Bisht; Jitender Kumar; Alka Kumari; Neha Neha; Sanya Chauhan; Arti Sharma; Rahul Kumar (Physiology and Molecular Biology of Plants, 2026)

Modeling and optimization for effective and selective removal of Victoria blue B dye from aqueous media using magnetic NiFe2O4 nanoparticles (NiFe2O4 NPs) - Pooja Rani; Sumeet Kumar; Monika Yadav; Sahil; Jitender Pal (Modeling Earth Systems and Environment, 2026)

Correction to: Ursolic Acid Emulgel Augmented Drug Delivery in Leishmania donovani, A Causative Agent for Cutaneous Leishmaniasis: In Vitro Characterization and Anti-Amastigote Activity - Spandana Gollapalli; Soyal Sayyed; Soham Loharkar; Atul Mourya; Gopal Bajad; Shristi Arya; Dinesh Kumar Chandanapalli; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Poly(ε-Caprolactone) Microparticles of Andrographolide for Paracetamol-Induced Liver Iinjury: Box-Behnken Design Based Optimization, In Vitro and In Vivo Studies - Nitin Wadate; Pawan Devangan; Pankaj Kumar; Gopal Bajad; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

First Report of Hb Oslo [HBB:c.127T>A; β42(CD1)Phe→Ile] from India and its Novel Compound Heterozygous Combination with IVS1–5 G>C [HBB:c.92+ 5G> C] Leading To β-Thalassemia Major - Deepti Malik; Kiran Thakur; Rakesh Kumar; Bhupender Kumar; Jitender Singh; Sadhna Sharma (Cell Biochemistry and Biophysics, 2026)

Ursolic Acid Emulgel Augmented Drug Delivery in Leishmania Donovani, A Causative Agent for Cutaneous Leishmaniasis: In Vitro Characterization and Anti-Amastigote Activity - Spandana Gollapalli; Soyal Sayyed; Soham Loharkar; Atul Mourya; Gopal Bajad; Shristi Arya; Dinesh Kumar Chandanapalli; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2025)

Deciphering pathological and population dynamics in Tilletia indica of Karnal bunt of wheat - Sangale Smita; Malkhan Singh Gurjar; Tej Pratap Jitendra Kumar; Jitender Kumar; Poulami Basak; Natasha Kashyap; Rahul Patidar; Muthyala Mahendra; Sri Ananth Kurella; Kartiki Sharma; Sundeep Kumar; Mahender Singh Saharan (Indian Phytopathology, 2025)

Genomics-assisted stacking of waxy1, opaque2, and crtRB1 genes for enhancing amylopectin in biofortified maize for industrial utilization and nutritional security - Subhra J. Mishra; Firoz Hossain; Rajkumar U. Zunjare; Rashmi Chhabra; Ashvinkumar Katral; Ikkurti Gopinath; Vinay Bhatt; Govinda Rai Sarma; Zahirul A. Talukder; Ravindra K. Kasana; Elangbam L. Devi; Konsam Sarika; et al. (Functional & Integrative Genomics, 2025)

Genome sequence of Bipolaris maydis inciting maydis leaf blight provides insights into genome architecture and putative effector repertoire - Poulami Basak; Malkhan Singh Gurjar; Tej Pratap Jitender Kumar; Natasha Kashyap; Sri Ananth Kurella; Muthyala Mahendra; Rahul Patidar; Sangale Smita; Kartiki Sharma; Robin Gogoi (Physiological and Molecular Plant Pathology, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

A culture-independent 16 S rRNA gene-based profiling of the sugarcane phyllosphere bacterial community in Western Uttar Pradesh, India - Aditya Pathak; Pankaj Kumar; Himanshu Kumar; Jitender Singh; Mahesh Kumar Bharti; Rekha Dixit; Kamal Khilari (World Journal of Microbiology and Biotechnology, 2025)

Exploring eco-friendly strategies for the management of blue mold of apple caused by Penicillium crustosum thom - Santosh Watpade; Isha Devi; Samadhan Yuvraj Bagul; G.N. Khadke; Dinesh Kumar; Hema Kumari; Rishav Kumar; Jitender Kumar; Kallol Kumar Pramanick; Dharam Pal; Priyank H. Mhatre; Santosh C. Kedar (Postharvest Biology and Technology, 2025)

RETRACTED ARTICLE: Molecular Approaches for Authentication and Identification of Medicinal Plants - Jitender Kumar; Kajal Choudhary; Shelja; Anukriti; Harsharan Singh; Ashwani Kumar; Pankaj Bagga (Plant Molecular Biology Reporter, 2025)

Unlocking therapeutic potential in traumatic brain injury: exploring microenvironmental targets, signaling pathways and translational hurdles - Deepankar Bahuguna; Etikala Amulya; Shristi Arya; Soham Loharkar; Ganesh Vambhurkar; Saptarshee Bhattacharjee; Dinesh Kumar Chandanapalli; Jitender Madan; Saurabh Srivastava (Inflammopharmacology, 2025)

Studies on the management of apple seedling blight (Sclerotium rolfsii Sacc.) through fungicides, botanicals, and nutrients - Santosh Watpade; Hema Kumari; Esha Devi; Dinesh Kumar; Rishav Kumar; Jitender Kumar; Priyank Hanuman Mhatre; K.K. Pramanick; Dharam Pal (Indian Phytopathology, 2025)

A Bayesian-based decision modeling approach for prioritizing barriers to sustainability in packaging supply chain - Gulshan Kumar Gaur; Jitender Madaan; Ekachidd Chungcharoen (Environment Systems and Decisions, 2025)

Bacterial Bioaerosol at Sewage Treatment Plant in Delhi, India: Characterization and Site-Specific Associations - Sunita Jakhar; Jitender Kumar Jakhar; Naba Hazarika; Arunangshu Das; Anil Pratap Singh; Arun Srivastava (Aerosol Science and Engineering, 2025)

Seismic attributes elucidating the geometry of subsurface faults: A case study from the upper Assam basin, NE India - Jitender Kumar; Bappa Mukherjee; Kalachand Sain (Journal of Earth System Science, 2025)

SnS2 integrated P-doped g-C3N4 with advanced photocatalytic efficiency towards organic pollutants decontamination - Monika Kumari; Naveen Kumar; Raj Kishore Sharma; Muhammad Tahir; Manickam Selvaraj; Pardeep Singh; Jitender Jindal; Anuj Mittal (Environmental Research, 2025)

Remediation of Chromium (III) and Cadmium (II) from the Aqueous Media by Algal-based Nanocellulose (A-CNF) - Sumeet Kumar; Monika Yadav; Pooja Rani; Sahil; Jitender Pal (Water Conservation Science and Engineering, 2025)

Assessment of natural mixed infection of turnip mosaic virus and cucumber mosaic virus on growth and yield of mustard genotypes - Pankhuri Singhal; Ronit Jaiswal; Ashwini Sakpal; Malyaj R. Prajapati; Virendra Kumar Baranwal; Sangita Yadav; Jitender Singh (Journal of Plant Diseases and Protection, 2025)

Gold Nanoparticles as a Tool to Detect Biomarkers in Osteoarthritis: New Insights - Atul Mourya; Shristi Arya; Ayush Singh; Gopal Bajad; Soham Loharkar; Shubhra; Pawan Devangan; Neelesh Kumar Mehra; Rahul Shukla; Ramesh Chandra; Jitender Madan (Indian Journal of Microbiology, 2025)

Unravelling the role of tumor microenvironment responsive nanobiomaterials in spatiotemporal controlled drug delivery for lung cancer therapy - Dadi A. Srinivasarao; Saurabh Shah; Paras Famta; Ganesh Vambhurkar; Naitik Jain; Sai Kiran S.S. Pindiprolu; Anamika Sharma; Rahul Kumar; Hara Prasad Padhy; Meenu Kumari; Jitender Madan; Saurabh Srivastava (Drug Delivery and Translational Research, 2025)

Revisiting cadmium-induced toxicity in the male reproductive system: an update - Jitender Kumar Bhardwaj; Anshu Siwach; Drishty Sachdeva; Som Nath Sachdeva (Archives of Toxicology, 2024)

Unsupervised learning approach for revealing subsurface tectono-depositional environment: A study from NE India - Priyadarshi Chinmoy Kumar; Heather Bedle; Jitender Kumar; Kalachand Sain; Suman Konar (Journal of Applied Geophysics, 2024)

Quercetin Supplementation Alleviates Cadmium Induced Genotoxicity-Mediated Apoptosis in Caprine Testicular Cells - Harish Panchal; Jitender Kumar Bhardwaj (Biological Trace Element Research, 2024)

Effect of plant growth regulators on morphology and physiology of Withania somnifera (L.) Dunal - Arti Jamwal Sharma; Sweta Punyal; Priyanka Sharma; Zishan Ahmad Wani; Shreekar Pant; Nitesh Kumar; Jitender Kumar; Somvir Singh (Vegetos, 2024)

Development of novel faba bean (Vicia faba L.) for release as a new cultivar with high yield and protein content - Rajesh K. Arya; Gajraj S. Dahiya; Ravi Kumar; Ranjeet K. Gill; Jitender K. Tiwari; Chander B. Yadav; Hanuman L. Raiger; Sandeep Kumar; Surya Kant (Genetic Resources and Crop Evolution, 2024)

Naringenin-Zinc Oxide Nanocomposites Amalgamated Polymeric Gel Augmented Drug Delivery and Attenuated Experimental Cutaneous Candidiasis in Balb/c Mice: In Vitro and In Vivo Studies - Chanti babu Katta; Deepankar Bahuguna; Harithasree Veerabomma; Spandana Gollapalli; Arbaz Sujat Shaikh; Nagesh A. Bhale; Amol G. Dikundwar; Venkat Rao Kaki; Pankaj Kumar Singh; Jitender Madan (AAPS PharmSciTech, 2024)

Porosity prediction using ensemble machine learning approaches: A case study from Upper Assam basin - Jitender Kumar; Bappa Mukherjee; Kalachand Sain (Journal of Earth System Science, 2024)

First report of cucumber mosaic virus (CMV) naturally infecting amaryllis (Hippeastrum hybridum) in India - Malyaj R Prajapati; Shivani Gupta; Jitender Singh; Pankaj Kumar; V. K. Baranwal (Journal of Plant Pathology, 2023)

Can adoption of climate resilient management practices achieve carbon neutrality in traditional green revolution states of Punjab and Haryana? - J.V.N.S. Prasad; V. Girija Veni; Ch. Srinivasarao; Sumanta Kundu; B. Ramakrishna; K. Sammi Reddy; Rajbir Singh; S.K. Singh; Ashish Santosh Murai; P.P. Rohilla; Gurpreet Singh Makkar; Vipan Kumar Rampal; et al. (Journal of Environmental Management, 2023)

Identification of a novel member of the Alphaendornavirus genus in Plantago ovata through transcriptome dataset mining - Malyaj R Prajapati; Jitender Singh; Pankaj Kumar; Ravindra Kumar; V.K. Baranwal (South African Journal of Botany, 2023)

Naringenin-Capped Silver Nanoparticles Amalgamated Gel for the Treatment of Cutaneous Candidiasis - Chantibabu Katta; Arbaz Sujat Shaikh; Nagesh Bhale; Vaskuri G. S. Sainaga Jyothi; Venkata Rao Kaki; Amol G. Dikundwar; Pankaj Kumar Singh; Renu Shukla; Krishnaveni Mishra; Jitender Madan (AAPS PharmSciTech, 2023)

Type 2 abomasal ulceration in cattle and buffalo: energy and lipid metabolic status, clinico-biochemical parameters, treatment, and prognostic indicators - Syed Ashaq Hussain; Sanjeev Kumar Uppal; Naresh Kumar Sood; Jitender Mohindroo (Tropical Animal Health and Production, 2023)

Andrographolide-Soya-L-α-Phosphatidyl Choline Complex Augmented Solubility and Drug Delivery in Leishmania donovani, a Causative Agent for Cutaneous and Visceral Leishmaniasis - Purva Pingle; Atul Mourya; Madhulika Namdeo; Katta Chanti Babu; Harithasree Veerabomma; Radheshyam Maurya; Pankaj Kumar Singh; Neelesh Kumar Mehra; Saurabh Srivastava; Jitender Madan (AAPS PharmSciTech, 2023)

Role of C4 photosynthetic enzyme isoforms in C3 plants and their potential applications in improving agronomic traits in crops - Jitender Singh; Sampurna Garai; Shubhashis Das; Jitendra Kumar Thakur; Baishnab Charan Tripathy (Photosynthesis Research, 2022)

First report of blackberry virus E (BVE) infecting garlic (Allium sativum L.) in India - Malyaj R Prajapati; Jitender Singh; Pankaj Kumar; V. K. Baranwal (Journal of Plant Pathology, 2022)

Studies on management of white root rot of apple caused by Dematophora necatrix - Santosh Watpade; Priyank Hanuman Mhatre; Kallol Kumar Pramanick; Arun Kumar Shukla; Jitender Kumar; Usha Sharma (Indian Phytopathology, 2022)

Effect of natural radionuclide’s in the environment along the Jwalamukhi thrust of Himachal Pradesh, North West Himalayas, India - Naveen Thakur; Reetika Bhadwal; Jitender Kumar; Manpreet Kaur; Rohit Mehra; Ajay Kumar (Environmental Geochemistry and Health, 2022)

First report of garlic mite-borne filamentous virus (GarMbFV) infecting garlic (Allium sativum L.) in India - Aakansha Manav; Malyaj R. Prajapati; Jitender Singh; Pankaj Kumar; Virendra Kumar Baranwal (Journal of Plant Pathology, 2022)

Amorphous systems for delivery of nutraceuticals: challenges opportunities - Devendrasingh Tomar; Pankaj K. Singh; Sajidul Hoque; Sheela Modani; Anitha Sriram; Rahul Kumar; Jitender Madan; Dharmendra Khatri; Kamal Dua (Critical Reviews in Food Science and Nutrition, 2022)

First report of natural infection by two potyviruses on amaryllis (Hippeastrum hybridum) plants from India - Aakansha Manav; Malyaj R. Prajapati; Jitender Singh; Amit Kumar; Pankaj Kumar; R. P. Pant; V. K. Baranwal (VirusDisease, 2021)

Establishment of virus-free elite mother orchards of apple in the Trans-Himalayan region of India - Santosh Watpade; Rakesh Kumar; Pooja Bhardwaj; Kallol Kumar Pramanick; Arun Kumar Shukla; Baswaraj Raigond; Jitender Kumar; Usha Sharma; Sumit Vashisth; Sudhir Verma (Indian Phytopathology, 2021)

Molecular identification of citrus greening bacterium associated with Kinnow Mandarin in Western Uttar Pradesh, India - Shweta; Jitender Singh; Poonam Kashyap; Pankaj Kumar; R. Kumar; A. S. Panwar; V. K. Baranwal (Indian Phytopathology, 2021)

Budding Multi-matrix Technology—a Retrospective Approach, Deep Insights, and Future Perspectives - Anitha Sriram; Suma Tangirala; Srividya Atmakuri; Sajid Hoque; Sheela Modani; Saurabh Srivastava; Srushti Mahajan; Indrani Maji; Rahul Kumar; Dharmendra Khatri; Jitender Madan; Pankaj Kumar Singh (AAPS PharmSciTech, 2021)

Isolation optimisation, synthesis, molecular docking and in silico ADMET studies of lantadene a and its derivatives - Sharad Kumar Suthar; Ajay Hooda; Ankesh Sharma; Sumit Bansal; Jitender Monga; Monika Chauhan; Manu Sharma (Natural Product Research, 2021)

Long-term sequelae of herpes simplex virus encephalitis–related white matter injury: correlation of neuropsychological outcome and diffusion tensor imaging - Gorky Medhi; Anish Kapadia; Subhendu Parida; Dhanya C; B. S. Bagepalli; Netravathi M; Keshav Kumar; Arun Kumar Gupta; Jitender Saini (Journal of NeuroVirology, 2021)

First report of 16SrXI-B subgroup phytoplasma in sapota showing flattened stem disease in India - Shailender Kumar; Jitender Singh; Virendra Kumar Baranwal; Govind Pratap Rao (Journal of Plant Pathology, 2021)

Carbon materials as CO2 adsorbents: a review - Anuradha Sharma; Jitender Jindal; Anuj Mittal; Kavitha Kumari; Sanjeev Maken; Naveen Kumar (Environmental Chemistry Letters, 2021)

Genome-wide association study for phosphate deficiency responsive root hair elongation in chickpea - Pawandeep Singh Kohli; Pankaj Kumar Verma; Rita Verma; Swarup K. Parida; Jitendra K. Thakur; Jitender Giri (Functional & Integrative Genomics, 2020)

Identification and Sequence-Based Validation of the EST-SSR Markers from Calotropis procera - Piush Srivastava; Tushar Pandey; Akansha Pandey; Jitender Kumar; Dipak Kumar Mishra; Anupam Dikshit; Vineeta Tripathi (Plant Molecular Biology Reporter, 2020)

Assessment of contaminants in the northwestern Bay of Bengal - Romi Nambiar; Chinmay Shah; Jitender Kumar; Pranav S. Shrivastav; Ravi Bhushan (Environmental Science and Pollution Research, 2020)

Resting state functional connectivity abnormalities and delayed recall performance in patients with amnestic mild cognitive impairment - Himanshu Joshi; Srikala Bharath; John P. John; Shilpa Sadanand; Jitender Saini; Keshav Kumar; Mathew Varghese (Brain Imaging and Behavior, 2020)

Aggregation, adhesion and efficacy studies of probiotic candidate Pediococcus acidilactici NCDC 252: a strain of dairy origin - Raman Kumar; Poonam Bansal; Jasbir Singh; Suman Dhanda; Jitender Kumar Bhardwaj (World Journal of Microbiology and Biotechnology, 2020)

Seismic attributes for characterizing gas hydrates: a study from the Mahanadi offshore, India - Jitender Kumar; Kalachand Sain; K. P. Arun (Marine Geophysical Research, 2019)

First report of association of begomovirus in yellow mosaic disease of bur cucumber in India - Shivani Khanna; Sonali Rana; Jitender Singh; Manisha Goyal; Pankaj Kumar; Neetu Singh; R. P. Pant; V. K. Baranwal (Indian Phytopathology, 2019)

Studies on Ectomycorrhiza: An Appraisal - Jitender Kumar; N. S. Atri (The Botanical Review, 2018)

Removal of Trinitrotoluene with Nano Zerovalent Iron Impregnated Graphene Oxide - Bharti; Ishani Khurana; Ajay Kumar Shaw; Amit Saxena; Jitender M. Khurana; Pramod Kumar Rai (Water, Air, & Soil Pollution, 2018)

Molecular characterization, modeling, in silico analysis of equine pituitary gonadotropin alpha subunit and docking interaction studies with ganirelix - Anuradha Bhardwaj; Varij Nayan; Parvati Sharma; Sanjay Kumar; Yash Pal; Jitender Singh (In Silico Pharmacology, 2017)
Equine pituitary gonadotropins (eLH, eFSH, eCG) are heterodimeric glycoprotein hormones with alpha (α) and beta (β) subunits. It is responsible for maintenance of pregnancy in mares during early gestation and fairly valuable for inducing superovulation in animals other than equines. The alpha subunit is common, while beta subunit is species-specific in all glycoprotein hormones. In the present investigation, molecular cloning and in silico characterization including homology modeling and molecular docking analysis of the equine chorionic gonadotropin (eCG) alpha subunit was carried out for gaining structural and functional insights into the eCG alpha subunit and its possible interaction with ganirelix, a gonadotropin-releasing hormone (GnRH) antagonist. The equine chorionic gonadotropin (eCG) alpha subunit expressed in pituitary gland was selected, amplified from total RNA, cloned and sequenced. The in silico analyses were made for homology modelling, structural details, epitope identification and chromosomal localization. Molecular docking studies of eCG alpha were undertaken with a drug ganirelix which is used to control ovulation and has antagonistic activity against GnRH. The protein sequence corresponding to selected open reading frame (ORF) was 99–100% similar with domesticated horse, Przewalski’s horse, and 92–93% with Burchell’s zebra and donkey. Molecular docking studies revealed the possible interaction of eCG alpha with ganirelix. The possible drug-macromolecule interactions were visualized between eCG alpha and ganirelix. The study will provide structural insight into unique sites and an alternate route of gonadotropin suppression applicable to assisted reproductive technologies.

Removal of Dyes Using Graphene-Based Composites: a Review - Ishani Khurana; Amit Saxena; Bharti; Jitender M. Khurana; Pramod Kumar Rai (Water, Air, & Soil Pollution, 2017)

Common Mechanism of Cross-Resistance Development in Pathogenic Bacteria Bacillus cereus Against Alamethicin and Pediocin Involves Alteration in Lipid Composition - Sunita Meena; Jitender Mehla; Raj Kumar; S. K. Sood (Current Microbiology, 2016)

Synthesis and biological evaluation of some functionalized 1H-1,2,3-triazole tethered pyrazolo[3,4-b]pyridin-6(7H)-ones as antimicrobial and apoptosis inducing agents - Jayant Sindhu; Harjinder Singh; J. M. Khurana; Jitender Kumar Bhardwaj; Priyanka Saraf; Chetan Sharma (Medicinal Chemistry Research, 2016)

Convenient synthesis, anticancer evaluation and QSAR studies of some thiazole tethered indenopyrazoles - Satbir Mor; Savita Nagoria; Ashwani Kumar; Jitender Monga; Sandeep Lohan (Medicinal Chemistry Research, 2016)

Animal models of hepatotoxicity - Ganesh Singh Bhakuni; Onkar Bedi; Jitender Bariwal; Rahul Deshmukh; Puneet Kumar (Inflammation Research, 2016)

Doppler Ultrasonography of Common Carotid Artery and External Jugular Vein in Healthy and Reticulo-Diaphragmatic Hernia Affected Buffaloes - Vandana Sangwan; Jitender Mohindroo; Ashwani Kumar; Chandra Sekhar Mukhopadhyay; Narinder Singh Saini (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Isolation and genetic characterization of Toxoplasma gondii from alpaca (Vicugna pacos) and sheep (Ovis aries) - Jitender Prakash Dubey; Sarah Jane Casey; Anne Marie Zajac; Stephen Arthur Wildeus; David Scott Lindsay; Shiv Kumar Verma; Solange Oliveira; Oliver Chun Hung Kwok; Chunlei Su (Tropical Animal Health and Production, 2014)

Effect of 3G Cell Phone Exposure with Computer Controlled 2-D Stepper Motor on Non-thermal Activation of the hsp27/p38MAPK Stress Pathway in Rat Brain - Kavindra Kumar Kesari; Ramovatar Meena; Jayprakash Nirala; Jitender Kumar; H. N. Verma (Cell Biochemistry and Biophysics, 2014)

Soil gas radon–thoron monitoring in Dharamsala area of north-west Himalayas, India using solid state nuclear track detectors - GULSHAN KUMAR; ARVIND KUMAR; VIVEK WALIA; JITENDER KUMAR; VIKASH GUPTA; TSANYAO FRANK YANG; SURINDER SINGH; BIKRAMJIT SINGH BAJWA (Journal of Earth System Science, 2013)

Analyses of diversity among fungicidal Anabaena strains - Vishal Gupta; Chitra Natarajan; Vidhi Chaudhary; Arun Kumar; Esha Sharma; Jitender Sharma; Ashok Kumar Bhatnagar; Radha Prasanna (Journal of Applied Phycology, 2012)

Economic impact of Przhevalskiana silenus infestation in native goats of Northern India - Anish Yadav; Rajesh Katoch; Jitender Kumar Khajuria; Meenu Katoch; Ankur Rastogi (Tropical Animal Health and Production, 2012)

Changes in Trace Elements during Follicular Atresia in Goat (Capra hircus) Ovary - Jitender Kumar Bhardwaj; Rajnesh K. Sharma (Biological Trace Element Research, 2011)

Iodine (III)-mediated synthesis of some 2-aryl/hetarylbenzoxazoles as antibacterial/antifungal agents - Ravi Kumar; Reshmi R. Nair; Saurabh Sudha Dhiman; Jitender Sharma; Om Prakash (Medicinal Chemistry Research, 2010)

Anti-dyslipidemic and antioxidant activities of different fractions of Pongamia pinnata (lin.) fruits - Gitika Bhatia; Anju Puri; Rakesh Maurya; Prem PrakashYadav; Mohammad Mubin Khan; Ashok Kumar Khanna; Jitender Kumar Saxena (Medicinal Chemistry Research, 2008)

Anti-dyslipidemic and antioxidant activities of different fractions of Pongamia pinnata (lin.) fruits - Gitika Bhatia; Anju Puri; Rakesh Maurya; Prem PrakashYadav; Mohammad Mobin Khan; Ashok Kumar Khanna; Jitender Kumar Saxena (Medicinal Chemistry Research, 2008)